PEMANFAATAN KARBON SEBAGAI FILTER UNTUK PENGENDALIAN PENCEMARAN AIR SUNGAI OLEH LOGAM Zn (seng) DARI LIMBAH PABRIK KELAPA SAWIT DI KABUPATEN KUANSING - Riad Syech; Restina Restina; Usman Malik (Komunikasi Fisika Indonesia, 2018)
A research has been conducated on using charcoal as a filter to control river water pollution with heavy metals from palm oil mill waste based on physical parameters in Kuantan Singingi district using SSA method. The process begin with taking sample from palm iol mill waste output, the the temperature and electrical conductivity of it is mesured. Heavy metal concentration (Zn) is mesured with Atomic Absorption (SSA). The highest electrical conductivity value before filtrasion was found in factory A sampel. The value is 8,87 x  10-4 Ωm-1with 0,241 mg/l Zn concetration. Electrical conductivity value decreased after filtration to 7,11 x 10-4 Ωm-1 with  0,216 mg/l mg/l Zn concetration. While the lowest electrical conductivity value before filtration was found in factory C sample. The value is 4,65 x 10-4 Ωm-1with 0,169 mg/l Zn consetration. Conductivity value decreased after filtration to 4,26 x 10-4 Ωm-1with 0,154 mg/l Zn contretation. These result explain that using charcoal as a filter for pollution control is uqite effective.